The Effect of Board Characteristics on Intellectual Capital: Case of Iran and Iraq - Hossien Shaval; Safoura Rouhi (Iranian Journal of Accounting, Auditing & Finance)
The present study is concerned about the relationship between the board characteristics and intellectual capital efficiency in companies listed on the Iran and Iraq Stock Markets.A multivariate regression model is used for this study. Research hypotheses were tested using a 903 firm-year observation sample from the Tehran Stock Exchange and 280 firm-year observations from the Iraq Stock Exchange during 2012-2018 for both counties based on multiple regression patterns and pooled data techniques. The results show that there is a significant relationship between board characteristics and efficiency of intellectual capital, which means there is a negative and significant relationship between the board independence, the board size, CEO ownership, and CEO gender, and intellectual capital and a positive and meaningful relationship between CEO change and intellectual capital both in Iran and Iraq. However, while the relationship between board independence and intellectual capital is negative in Iraq, such a relationship is positive and significant in Iran.